Development of Interactive e-Worksheet to Improve Science Process Skills of Junior High School Students - Mayasari, Indah; Setyarini, M.; Diawati, Chansyanah (Jurnal Pendidikan MIPA, 2023)
This study aims to develop interactive worksheet, describe the validity, practicality, and effectiveness of interactive worksheet by using liveworksheets to improve junior high school students' science process skills in the material of additives and addictive substances . The research method uses the 4-D development model. The subjects of this study were 66 students consisting of 32 students in class VIII A and 34 students in class VIII B at Gajah Mada Junior High School. The instruments used in this study were questionnaires and tests. Questionnaires are used to obtain validation data, test student responses and teacher responses while tests are used to measure effectiveness by collecting pre-test and post-test data. The results of this research and development indicate that the results of the validation of material and media experts obtained a percentage of 88% in the valid category. Practical interactive worksheets are used with a percentage of values with very practical criteria. This interactive worksheet is also effective for improving students' science process skill in the experimental class with an average N-Gain of 0.72 with a high classification and the effect size value is 0.94 with the big category. Keywords: liveworksheet, interactive worksheet, science process skill, discovery learningDOI: http://dx.doi.org/10.23960/jpmipa/v24i1.pp321-329